2009
DOI: 10.1002/ptr.2489
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of an essential oil mouthrinse on plaque, gingivitis and salivary Streptococcus mutans levels: a double blind randomized study

Abstract: An open, randomized, controlled study with two parallel treatment groups was done to evaluate the efficacy of a Lippia sidoides essential oil (EO) 1% mouthrinse compared with chlorhexidine 0.12% mouthrinse, applied two times daily for 1 week, in the treatment of dental plaque and gingivitis. Fifty-five patients were included in the study. The efficacy variables were the colony count of Streptococcus mutans from the stimulated saliva and periodontal indices on days 0, 7 and 30 after commencement of therapy. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 18 publications
(23 reference statements)
3
55
0
2
Order By: Relevance
“…Thymol has been the main component found and might be associated with the antimicrobial activity presented by that natural product (Fontenelle et al, 2007). Botelho et al (2009) also demonstrated that the essential oil from the leaves of L. sidoides (1%) is responsible for a decrease in the levels of salivary mutans streptococci.…”
Section: Main Authormentioning
confidence: 92%
See 1 more Smart Citation
“…Thymol has been the main component found and might be associated with the antimicrobial activity presented by that natural product (Fontenelle et al, 2007). Botelho et al (2009) also demonstrated that the essential oil from the leaves of L. sidoides (1%) is responsible for a decrease in the levels of salivary mutans streptococci.…”
Section: Main Authormentioning
confidence: 92%
“…Of the studies that showed satisfactory results, only Rassameemasmaung et al (2007), Botelho et al (2008) and Botelho et al (2009) specify which part of the plant was used in the mouthrinse formulation.…”
Section: Main Authormentioning
confidence: 99%
“…Essential oils exert many properties such as antinociceptive (Franco et al, 2011), anticonvulsant (Oliveira, 2009), cardiovascular effects (Menezes et al, 2010), antimicrobial activity against cariogenic bacteria (Botelho et al, 2009a) and fungal fi laments as well (Botelho et al, 2007b). Some studies point out that those plant-derived essential oils may be an effective alternative to overcome microbial resistance (Botelho et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They were also used in medical treatments and were known for exhibiting antimicrobial properties such as antifungal, antibacterial, antiviral and antiparasite (Fuselli et al, 2008;Botelho et al, 2007c;Botelho et al,2009a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation